2012
DOI: 10.1128/aem.06444-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Assays for Sensitive and Reproducible Detection of Cell Culture-Infectious Cryptosporidium parvum and Cryptosporidium hominis in Drinking Water

Abstract: This study compared the three most commonly used assays for detecting Cryptosporidium sp. infections in cell culture: immunofluorescent antibody and microscopy assay (IFA), PCR targeting Cryptosporidium sp.-specific DNA, and reverse transcriptase PCR (RT-PCR) targeting Cryptosporidium sp.-specific mRNA. Monolayers of HCT-8 cells, grown in 8-well chamber slides or 96-well plates, were inoculated with a variety of viable and inactivated oocysts to assess assay performance. All assays detected infection with low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 27 publications
0
29
0
3
Order By: Relevance
“…In the case of the qPCR assay, background signal due to high inoculum densities is the major concern (Di Giovanni & LeChevallier, 2005). Hence, higher infection rates detected by the PCR assay may be the result of a relatively high frequency of false positives (Johnson et al, 2012). Additionally, growth supplements such as glucose and vitamins used in the inoculum for PCR assays have also been reported as major contributing factors in to increased C. parvum cell culture infection.…”
Section: Analysis Techniques For the Evaluation Of Viabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of the qPCR assay, background signal due to high inoculum densities is the major concern (Di Giovanni & LeChevallier, 2005). Hence, higher infection rates detected by the PCR assay may be the result of a relatively high frequency of false positives (Johnson et al, 2012). Additionally, growth supplements such as glucose and vitamins used in the inoculum for PCR assays have also been reported as major contributing factors in to increased C. parvum cell culture infection.…”
Section: Analysis Techniques For the Evaluation Of Viabilitymentioning
confidence: 99%
“…A comparison of RT-PCR and immunofluorescence assay (IFA) and microscopy assay (DAPI/PI) for testing viability suggested that RT-PCR is better for viability detection in Giardia, whereas IFA is superior for detecting viable Cryptosporidium oocysts (Johnson et al, 2012). Other molecular assays, such as FISH and nucleic acid probes, can be used to detect 18S rRNA in Giardia and Cryptosporidium.…”
Section: Progress In Cryptosporidium Viability Analysismentioning
confidence: 99%
See 3 more Smart Citations